THE INTERRELATION OF AQIDAH, SHARIA, AND MORALITY IN THE PERSPECTIVE OF USTADZ ABDUL SOMAD - Satra, Alihan; Assah, Hafidzah; Azzahra, Aliffia Putri; Jeny, Aliya; Sari, Ginanda Putri Indah (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study explores the integrated relationship between Aqidah (Islamic creed), Sharia (Islamic law), and Akhlaq (morality) as fundamental components of Islam that form a unified framework of religious life. Employing a qualitative method through literature review and content analysis, this research focuses on the perspective of Ustadz Abdul Somad. The findings reveal that, according to Abdul Somad, Aqidah serves as the foundational belief underpinning all aspects of life. Sharia represents the practical implementation of Aqidah through acts of worship and legal rulings, while Akhlaq emerges as the ethical outcome of adhering to Sharia rooted in a firm Aqidah. These three elements are hierarchically and functionally interconnected: Aqidah motivates the practice of Sharia, which in turn cultivates noble character. The study underscores the importance of an integrated Islamic educational approach that harmonizes these three dimensions to shape a balanced Muslim personality. The findings contribute to a deeper understanding of the unity between belief, practice, and ethics in Islam. Penelitian ini mengkaji hubungan terintegrasi antara Aqidah (keimanan), Syariah (hukum Islam), dan Akhlaq (moral) sebagai tiga komponen fundamental dalam Islam yang membentuk satu kesatuan dalam praktik kehidupan beragama. Penelitian ini menggunakan metode kualitatif melalui studi pustaka dan analisis isi terhadap pandangan Ustadz Abdul Somad. Hasil penelitian menunjukkan bahwa menurut Abdul Somad, Aqidah merupakan dasar keyakinan yang melandasi seluruh aspek kehidupan. Syariah merupakan manifestasi praktis dari Aqidah melalui ibadah dan hukum Islam, sedangkan Akhlaq adalah buah dari pelaksanaan Syariah yang didasari oleh Aqidah yang kuat. Ketiganya saling terhubung secara hierarkis dan fungsional: Aqidah mendorong pelaksanaan Syariah, yang pada gilirannya melahirkan akhlak yang mulia. Studi ini menekankan pentingnya pendekatan pendidikan Islam yang integratif untuk membentuk kepribadian Muslim yang seimbang. Temuan ini memperkaya wawasan keislaman dan memperkuat pemahaman masyarakat akan kesatuan antara keimanan, ibadah, dan moralitas dalam Islam.